MEASURING THE IMPACT OF EXCHANGE RATE CHANGES ON IMPORTED INFLATION IN IRAQ - Hussein Abed Shanan Hashem (Scholar Express Journals, 2024)
To achieve the research objectives, the descriptive and deductive approach was used. The most significant findings are that the Iraqi economy is viewed as a one-sided economy and that it primarily depends on oil exports. The research also aims to shed light on the concept and importance of the exchange rate, as well as imported inflation and transmission channels through the rise in global prices compared to local prices, as well as identifying the most important effects of hidden inflation and the ways that can be relied upon to reduce its severity. This is supported by the fact that import inflation raises investment costs, as evidenced by the rise in import volume following increases in oil export prices and quantities. local and unequal wealth and income distribution among society's constituents. The most important recommendations were to work to reduce the value of the Iraqi dinar against the dollar and thus have a positive and significant impact on the balance of payments, and to work to simplify government procedures and encourage commercial competition with regard to local products, and thus reduce dependence on imports from abroad in order to reduce the severity of the economic crises that could occur. That the Iraqi economy is exposed to it.
Keywords: Exchange rate; exchange rate functions; imported inflation